PENGEMBANGAN PERANGKAT LUNAK ANALISIS LINTAS TERBANG ROKET MULTI-STAGE (DEVELOPMENT OF TRAJECTORY ANALYSIS SOFTWARE FOR MULTI-STAGE ROCKET) - Poetro, Ridanto Eko; Jenie, Yazdi I; Sasongko, Rianto Adhy; Utama , Satriya (BRIN Publishing, 2012)
This paper discusses the development of a computer software for simulating and analyzing flight trajectory of rocket systems. Many aspects may influence the trajectory, such as those related to the internal characteristic of the system, those representing external or environmental influence, and also the ones corresponding to the procedures of the launching and the operation during its flight. The software is developed based on the mathematical equations representing the balance of forces and moments occur during the flight of a rocket. Some conditions related to rocket internal characteristic variation, external perturbance, and flight procedure/operation are represented as parameters variations of the mathematical equations used for computing the rocket system attitude and movement variables. The software, developed using MATLAB/ SIMULINK application, is then used for simulating and analyzing the flight trajectory of a multi-stage rocket in some flight conditions. At this development stage, as the simulation results show, the software can perform its function quite well to compute the system variables during each of its flight phases and display the information required for further analysis. In future development, some validation tests still need to be accomplished for ensuring the accuracy and validity of the method used in this software.